AVALIAÇÃO DOS ESTÁDIOS DE MATURAÇÃO DOS FRUTOS DA PALMEIRA Euterpe edulis MARTIUS - Fornazzari, Isis Mariane (2011)
The palm tree Euterpe edulis is a kind of middle stratum of the forest Atlantic with high economic value as food. This study aimed to evaluate the ripeness stage the fruits this palm from five properties located in the municipal district of Antonina, in Paraná, Brazil,aiming to improve crops of these fruits. Physical characterizations were performed in whole fruits and physico-chemical pulp dehydrated. The methods used to characterize the phytochemicals compounds were the Folin-Ciocalteau methods for phenolic compounds, the pH differential method and FRAP for anthocyanins and the antioxidant activity in fruit pulp integrals. The characterization results physical diameters and indicated different weights for fruits collected in different clusters of the same plant. The maturation began in February only two of the sampling sites. The cycles ended at the end of May at four places and the fruits of one of the properties had not yet shown signs of ripeness. This diversity of characteristics can be related to the environmental aspects of each the area of collect, which somehow can be influence the biochemical changes in fruits. The antioxidant activity was highly variable over the 135 days of study because it may depend on several intrinsic and extrinsic factors that may be associated with biochemical changes resulting from the ripeness that allows an expense or an accumulation of these compounds in fruits.